The NIRVANDELS Survey: a robust detection of α-enhancement in star-forming galaxies at z ≃ 3.4. Issue 1 (12th May 2021) - Cullen, F; Shapley, A E; McLure, R J; Dunlop, J S; Sanders, R L; Topping, M W; Reddy, N A; Amorín, R; Begley, R; Bolzonella, M; Calabrò, A; Carnall, A C; et al.
ABSTRACT: We present results from the NIRVANDELS survey on the gas-phase metallicity ( Z g, tracing O/H) and stellar metallicity ( Z ⋆, tracing Fe/H) of 33 star-forming galaxies at redshifts 2.95 < z < 3.80. Based on a combined analysis of deep optical and near-IR spectra, tracing the rest-frame far-ultraviolet (FUV; 1200–2000 Å) and rest-frame optical (3400–5500 Å), respectively, we present the first simultaneous determination of the stellar and gas-phase mass–metallicity relationships (MZRs) at z ≃ 3.4. In both cases, we find that metallicity increases with increasing stellar mass ( M ⋆ ) and that the power-law slope at M ⋆ ≲ 10 10 M⊙ of both MZRs scales as Z M_^0.3 . Comparing the stellar and gas-phase MZRs, we present direct evidence for super-solar O/Fe ratios (i.e. α-enhancement) at z > 3, finding (O/Fe) = 2.54 ± 0.38 × (O/Fe)⊙, with no clear dependence on M ⋆ .